Strategic management models and resource-based strategies among mnes in a host market - Tallman, Stephen (Strategic Management Journal, 1991)
This article develops a resource-based strategic management model of MNE market entry. Strategic groups of firms in the U.S. foreign auto industry are derived empirically and tested for their ability to explain structural and performance results in one industry and one host country under the assumptions of the model.